Foot Reflexology Interventions for Blood Pressure Control in Hypertensive Individuals: A Locality-Specific Analysis in Pekauman Ward, RT.15 - Agustina, Anita; Putri, fadila Auliya; Kurniati, Titi; Oktiyawati, Emi; Saipurahman, Saipurahman; Wijaya, Wisnu (UrbanGreen Central Media, 2025)
Hypertension is characterized by a systolic blood pressure (SBP) of at least 130 mm Hg and/or a diastolic blood pressure (DBP) exceeding 80 mmHg. Foot reflexology has demonstrated effectiveness in lowering heart rate (HR) among patients with stage 2 hypertension, and it has also been partially effective in reducing blood pressure. This research aimed to examine the impact of foot reflexology massage on decreasing blood pressure in hypertensive individuals. The intervention involved providing reflexology massage to a randomly selected group of 20 participants. Blood pressure readings were collected before and after the intervention. Statistical analysis using the paired sample t-test revealed a significant reduction in blood pressure, with a p-value below 0.001. Based on these findings, it is suggested that people with hypertension practice foot reflexology independently at home, and that healthcare providers at community health centers deliver education about the benefits of this therapy in managing blood pressure.